Liver transplantation in glycogen storage disease type III: A case‐series - Simon Gay; Adrien Bigot; Louis d'Alteroche; Fanny Dujardin; Gaëlle Fromont‐Hankard; Nathalie Tressel; Ephrem Salame; François Maillot (JIMD Reports)
Abstract Glycogen storage disease type III (GSD III) is a rare metabolic disorder characterized by a deficiency of liver and muscle amylo‐1,6‐glucosidase. This condition presents with severe hepatic symptoms in childhood, mostly hepatomegaly, hypoglycemia in half of patients, while muscular complications may predominate in adulthood. Hepatic fibrosis, cirrhosis and hepatocellular carcinoma (HCC) are common complications in older patients. Therefore, regular monitoring, including HCC screening, is essential for effective disease management. In some severe cases, liver transplantation (LT) may be necessary to treat life‐threatening complications. Here, we report the cases of three adult patients who required LT during the course of GSD III. Case #1: Diagnosis of GSD III was made in childhood, with development of hepatocellular carcinoma requiring partial hepatectomy followed by LT due to post‐operative complications. The patient recovered well and had favorable surveillance over a seven‐year period. Case #2: Diagnosis of GSD III in early childhood, with progression to cirrhosis in adulthood. Severe hepatic encephalopathy necessitated urgent transplantation, with a favorable recovery, although muscular symptoms remained present. Case #3: Diagnosis of GSD III in childhood, followed by later development of hepatocellular adenocarcinoma requiring LT. The patient recovered well and did not exhibit post‐transplant muscular symptoms. Post‐LT outcome was positive for all three GSD III patients, with significant improvement in liver function and no complications related to immunosuppression. Long‐term hepatic monitoring is essential for early detection of complications such as cirrhosis and HCC. LT indications should be individually evaluated, preferring less invasive options. These cases highlight the importance of a multidisciplinary approach to the effective management of GSD III, with particular attention to hepatic and muscular surveillance.